Restoring drug sensitivity in colorectal cancer through Cdc42 inhibition - Yermekova , Aislu; Sailauova , Aibanu; Umbayev , Bauyrzhan; Zhuraliyeva, Altyn (Eurasian Journal of Applied Biotechnology, 2025)
Background: Colorectal cancer (CRC) remains a leading cause of cancer mortality, and therapeutic failure is often driven by resistance to chemotherapy. Cdc42-a is a small Rho GTPase that regulates cell survival, cytoskeletal dynamics, and stress responses and has emerged as a plausible target for reversing chemoresistance in CRC. Materials and methods: Non-resistant (NR) and doxorubicin-resistant (DOX-R) LoVo cells were generated by stepwise doxorubicin escalation and validated by IC50 determination (NR: 0.1398 µM; DOX-R: 0.5281 µM). Cells were treated for 48 h with CASIN (a Cdc42 inhibitor; 5 µM), doxorubicin (at each line’s IC50), or the combination. Cell viability was measured by Alamar Blue. Cdc42 activity was quantified using a G-LISA assay, and intracellular doxorubicin was assessed fluorometrically. Results: CASIN alone did not significantly alter viability in either NR or DOX-R cells. In contrast, CASIN plus doxorubicin markedly reduced viability in both models, lowering DOX-R cell survival to <10% of control-consistent with restored drug sensitivity. Basal Cdc42 activity was comparable between NR and DOX-R cells, indicating resistance was not driven by elevated Cdc42 activation. CASIN did not increase intracellular doxorubicin, suggesting the chemosensitizing effect occurs independently of altered drug uptake or efflux. Conclusion: Pharmacologic Cdc42 inhibition with CASIN substantially restores doxorubicin responsiveness in resistant CRC cells through mechanisms unrelated to drug transport. These findings support Cdc42 targeting as a promising approach to overcome chemoresistance in CRC. Acknowledgements: This research has been funded by the Science Committee of the Ministry of Science and Higher Education of the Republic of Kazakhstan (Grant No. AP26100973) and Nazarbayev University, Collaborative Research Project (CRP) Grant No. 211123CRP1611. Key words: colorectal cancer, chemoresistance, cdc42, CASIN, Doxorubicin, IC50 References: Zhylkaidarova, A.; Kaidarova, D.; Batyrbekov, K.; Shatkovskaya, O.; Begimbetova, D. Trends of Colorectal Cancer Prevalence in Kazakhstan Related to Screening. Clin Endosc 2021, 54, 32-37, doi:10.5946/ce.2019.198. Sakamori, R. et al. (2014) ‘CDC42 inhibition suppresses progression of incipient intestinal tumors’, Cancer Research, 74(19), pp. 5480–5492. doi:10.1158/0008- 5472.can-14-0267. Tacar, O., Sriamornsak, P., & Dass, C. R. (2013). Doxorubicin: an update on anticancer molecular action, toxicity and novel drug delivery systems. Journal of Pharmacy and Pharmacology, 65(2), 157-170. doi:10.1111/j.2042-7158.2012.01567.